2018
DOI: 10.1159/000493629
|View full text |Cite
|
Sign up to set email alerts
|

PINK1/Parkin-Mediated Mitophagy Promotes Resistance to Sonodynamic Therapy

Abstract: Background/Aims: Sonodynamic therapy (SDT), based on the synergistic effect of low-intensity ultrasound and sonosensitizer, is a potential approach for non-invasive treatment of cancers. In SDT, mitochondria played a crucial role in cell fate determination. However, mitochondrial activities and their response to SDT remain elusive. The purpose of this study was to examine the response of mitochondria to SDT in tumor cells. Methods: A human breast adenocarcinoma cell line - MCF-7 cells were subjected to 5-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…In this review, PS mapping for tumor PDT can be roughly divided into three areas: Mitochondria[ 69 - 78 ], endoplasmic reticulum[ 12 , 68 , 79 - 82 ], and lysosomes[ 83 - 88 ]. These PSs can be roughly summarized into porphyrin-based photosensitizers, such as porphyrins[ 89 - 92 ], chlorins[ 80 , 93 , 94 ], phthalocyanines, and naphthalocyanines[ 95 - 99 ], and non-porphyrin-based photosensitizers, such as cyanine, methylene blue, Nile blue, rhodamine, triarylmethane, and acridine[ 68 , 100 - 105 ]. These PSs and their derivatives are summarized by category in Table 1 .…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%
“…In this review, PS mapping for tumor PDT can be roughly divided into three areas: Mitochondria[ 69 - 78 ], endoplasmic reticulum[ 12 , 68 , 79 - 82 ], and lysosomes[ 83 - 88 ]. These PSs can be roughly summarized into porphyrin-based photosensitizers, such as porphyrins[ 89 - 92 ], chlorins[ 80 , 93 , 94 ], phthalocyanines, and naphthalocyanines[ 95 - 99 ], and non-porphyrin-based photosensitizers, such as cyanine, methylene blue, Nile blue, rhodamine, triarylmethane, and acridine[ 68 , 100 - 105 ]. These PSs and their derivatives are summarized by category in Table 1 .…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%
“…Recent study has found that hepatic fatty acid accumulation can cause damaged mitochondria accumulation, which can impair mitochondrial respiratory chain function and fatty acid oxidative degradation (Ashrafi and Schwarz, 2013; Wu et al, 2015). Surprisingly, PINK1/Parkin-mediated mitophagy can reverse mitochondrial dysfunction and preserve mitochondrial function through eliminating damaged mitochondria in time (Wu et al, 2015; Nguyen et al, 2016; Xiong et al, 2018; Song et al, 2018a; Wang et al, 2019a).…”
Section: Signaling Pathways Involved In Mitophagymentioning
confidence: 99%
“…Mitophagy plays an important role in maintaining a healthy population of mitochondria by ensuring that there is an optimal balance between mitochondrial biogenesis and turnover [5,6]. Recently, the involvement of Parkin-mediated mitophagy in nephropathy has come to light [7,8]. In this mitophagy process, Parkin, which is an E3 ubiquitin ligase, is transported from the cytoplasm to depolarized mitochondria, where it subsequently induces the autophagic degradation of dysfunctional mitochondria.…”
mentioning
confidence: 99%